2018
DOI: 10.1111/psyp.13308
|View full text |Cite
|
Sign up to set email alerts
|

Threat‐conditioned contexts modulate the late positive potential to faces—A mobile EEG/virtual reality study

Abstract: In everyday life, the motivational value of faces is bound to the contexts in which faces are perceived. Electrophysiological studies have demonstrated that inherent negatively valent contexts modulate cortical face processing as assessed with ERP components. However, it is not well understood whether learned (rather than inherent) and three‐dimensional aversive contexts similarly modulate the neural processing of faces. Using full immersive virtual reality (VR) and mobile EEG techniques, 25 participants under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 100 publications
4
53
0
Order By: Relevance
“…In recent years, EEG use has increased, with 6 papers being published (14.3%), and the CNS has started to be used, in combination with HMDs, to recognise emotions. The analyses that have been used are ERP [ 138 ], power spectral density [ 140 ] and functional connectivity [ 65 ]. EMG (11.9%) and RSP (9.5) were also used, mostly in combination with HRV.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, EEG use has increased, with 6 papers being published (14.3%), and the CNS has started to be used, in combination with HMDs, to recognise emotions. The analyses that have been used are ERP [ 138 ], power spectral density [ 140 ] and functional connectivity [ 65 ]. EMG (11.9%) and RSP (9.5) were also used, mostly in combination with HRV.…”
Section: Resultsmentioning
confidence: 99%
“…In more recent years, advances in HMD technologies have positioned HTC Vive as the most used (19.05%). In terms of formats, 3D environments are the most used [ 138 ] (85.71%), with 360° panoramas following far behind [ 142 ] (16.67%). One research used both formats [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, future development of 3D or 4D databases for experimental designs, can further improve stimuli by being built as full-volumes and not surfaces. For example, the database presented in Figure 2B, experiences a loss of data from the posterior viewpoint of the head, which may impede studies examining VR environments (Bulthoff and Edelman, 1992;Stolz et al, 2019;Lamberti et al, 2020) or multiple viewpoints of a facial stimulus (Bülthoff et al, 2018;Abudarham et al, 2019;Zhan et al, 2019). Overall, despite some remaining challenges, 3D and 4D facial capture and reconstruction has demonstrated that the unique facial features belonging to you and me, such as the cheeks, eyes and nose, can simulated on-screen in a highly realistic manner (see Figure 2).…”
Section: How Are 3d and 4d Facial Databases Captured And Reproduced Imentioning
confidence: 99%